The regulated firm: Effects of regulation on competence development and sustainable competitive advantage - Torsten Frohwein (Universität Stuttgart, Betriebswirtschaftliches Institut, Abteilung I - Forschungs-, Entwicklungs- und Innovationsmanagement, 2015)
Sustainable competitive advantage (SCA) is a central tenet in strategic management theory. The effect of regulation on sustaining competitive advantages is widely neglected in literature. The impact on competence development and SCA of the firm can be significant, if regulatory requirements and regulatory prohibitions as types of specific industry regulation are considered. In arguing that resource-based theory can be modeled analogous to complex system theory, the effect of regulation on competence development and SCA is illustrated. In explaining the effect of regulation on competence development and SCA, the paper contributes to close a gap in one of the central assumptions of attaining SCA resource-based theory.
Keywords: 650; strategic management; resource-based theory; sustainable competitive advantage; competence development; regulation; open system